Cachimbas and Kitras: An Approach to the Smoking Practices of the Ceramic Groups of the Center-Southern Area of Chile [Cachimbas y Kitras: Un Acercamiento a Las Prácticas Fumatorias de Grupos Alfareros del Centro-Sur de Chile] - Echeverria-Morgado, J (Universidad de Magallanes, 2017)
Archaeological and ethnohistorial data show that smoking practices in the central-southern region of Chile begins during the Early Ceramic period and continue until historical times. In view of this long time span, twelve smoking pipes were studied: their morphology and decoration were determined, and use residues were analyzed to unravel the elements consumed. Considering the importance of smoke in the mapuche world, a pichimetawe and an undetermined ceramic fragment where also studied. Results show seven types of smoking pipes for the area. It was possible to identify the presence of Nicotiana sp., Cyperaceae and cf. Latua pubiflora in some of these artifacts.